ALGAL DYNAMICS OF RIVER PANDU IN RELATION TO AMBIENT ENVIRONMENT - Verma, Sunita; Tiwari, Divya; Verma, Ajay (Ecoprint: An International Journal of Ecology, 2014)
An investigation on river Pandu in the year 2009-2010 was carried out to explore its current status in terms of physico-chemical and phycological profile. The study revealed that algal spectrum of the river was connected with the intensity of pollution in the river. River, at present is a perturbed ecosystem due to heavy anthropogenic stress on it. Despite abundant nutrients and other factors responsible for propping algal growth, river had a meak algal population and low diversity as compared to other perennial rivers indicating the grossly polluted unhealthy condition of the river. Algae are natural inhabitants of aquatic environment; and act as natural purifiers due to their nutrient gleaning and oxygenating capabilities; they are more sensitive than animals to industrial and municipal wastes. Maximum number of species existed at station-1 followed by stations-4 and 6 and then at station-5. Lowest species representation has been noticed at stations-2 and 3. Species number and algal population too declined sharply at stations-2 and 3 as compared to station-I. Sharp decline in algal population at stations-2 and 3 may be attributed to certain obvious reasons such as low transparency and reduced illumination as a consequence of residual fly ash discharged by PTPP drain at station-2. Except station-1, all downstream stations show grossly polluted condition of the river. DOI: http://dx.doi.org/10.3126/eco.v20i0.11325 Ecoprint: An International Journal of Ecology Vol. 20, 2013 Page : 9-17